Assessment of Traditional Practices Aggravating Maternal Mortality in Temeke District, Tanzania - Mbwana, E.; Kivelia, J. (Tanzania Journal for Population studies and Development, 2010)
A study to assess traditional practices aggravating maternal mortality in urban and mixed rural-urban populations was carried out in Toangoma and Tandika Wards in Temeke District. Data were collected using questionnaire interviews, un-structured interviews, and in-depth interviews. Data collected were mainly qualitative, and this necessitated use of content analysis. In addition, quantitative analyses were also performed where necessary. Findings indicate that most maternal deaths and complications were associated with cases of anaemia, eclampsia and haemorrhage. The factors behind were more less related to traditional practices. Young age at birth, poor nutrition associated with taboos on types of foods to be eaten during pregnancy, as well as short child spacing instigated by preference of male children were the main factors behind problems related to anaemia and women failure to push during delivery. Also, poverty and lack of control over household resources, male dominated decisions on when and where to seek medical help, and adherence to other cultural norms and values are part of the traditional practices that acted as barriers on women towards seeking modern medical care. Other traditional practices aggravating maternal mortality in the area include belief systems on the causes and cures of diseases. The study recommends that people should be given more modern education about maternal problems associated with over-reliance on traditional practices, right kind information about traditional medicines and herbs, and the discouragement of early marriage to alleviate the problem.